The extent of Concern of the University Press in Students’ Issues (Journal of the University of Technology as a Model) for the Period from 2009 to 2012 - Jassim, Hadeel Fouzi (ALBAHITH ALALAMI, 2013)
The university press is an essential pillar in building an academic community to achieve its objectives in the service of society. Since the university press is a means of university media, which is issued by the departments or units of media in Iraqi universities as academic governmental-institutions, so it highlights the activities of the university and link them to its internal society in the first place as the university press is a mirror of the university and its voice is sincerely expressed. This research comes to know the extent of interest of the university press in various student issues.In order to identify the problem of the research, the method of content analysis was adopted within the survey method. The content of the news report, moreover, was analyzed in the Journal of the University of Technology for the period from 2009 to 2012. The researcher has reached a set of results, the most important of which are:The university press represented by the Journal of the University of Technology did not pay much attention to the issues of students. So, we should pay more attention to the affairs of students, because they are an effective element in Iraqi universities.The magazine focused on the scientific issues of the students more than other issues. Where scientific issues came in first place, followed by sports issues in second place, and then service issues got third place. Whereas, educational and health issues came in fourth place, and finally technical issues and other issues ranked fifth.The categories of supporting students' scientific projects and focusing on honoring top students of a total number of repetitions of scientific issues ranked first. The category of university students to practice sports ranked in the first place among sports issues. While service issues included the category of demand to provide the necessary services to students ranked first. The category of claiming to provide health care and education to students also received the first rank among educational and health issues. Among the technical cases, the category of affirmation of the students' practice of works of art was ranked first. While condemning terrorist acts affecting students ranked first among other cases.Despite the irregular issuance of the magazine due to several reasons, it has witnessed a gradual development in terms of increasing the number of pages; and innovating new sections to suit the development occurred in the university.